2020
DOI: 10.1371/journal.pone.0234521
|View full text |Cite
|
Sign up to set email alerts
|

The weekend effect for stroke patients admitted to intensive care: A retrospective cohort analysis

Abstract: Objectives To examine the effect of weekend admission on short and long-term morbidity and mortality, for patients admitted to intensive care after suffering a cerebrovascular accident (stroke). Design, setting, and participants A hospital-wide, retrospective cohort study of 3,729 adult stroke patients admitted to the Beth Israel Deaconess Medical Centre (BIDMC) intensive care unit (ICU) between 2001 and 2012, using the Medical Information Mart for Intensive Care III (MIMIC-III) database. Primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…16,25,26 Additional subpopulations studies of critically-ill patients (eg, surgical ICUs, cardiac ICUs, and patients with strokes) have also found suggestions of a weekend effect. 15,16,18,19,25,26 The findings of our study are particularly unanticipated given the focus on patients receiving MV, a fundamentally sicker population than has been previously studied and one that may be more vulnerable to potential fluctuations in hospital resources on weekends (eg, respiratory therapy or nurse staffing).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…16,25,26 Additional subpopulations studies of critically-ill patients (eg, surgical ICUs, cardiac ICUs, and patients with strokes) have also found suggestions of a weekend effect. 15,16,18,19,25,26 The findings of our study are particularly unanticipated given the focus on patients receiving MV, a fundamentally sicker population than has been previously studied and one that may be more vulnerable to potential fluctuations in hospital resources on weekends (eg, respiratory therapy or nurse staffing).…”
Section: Discussionmentioning
confidence: 90%
“…However, studies have shown mixed results with several demonstrating increased mortality in weekend ICU admissions, possibly mediated by care complications such as delays to ICU bed placement, health care associated pneumonia (HAP), and reintubation. [15][16][17][18][19][20] Conversely, other studies have not shown an association. [21][22][23] These varied results are reflected in systematic reviews and metaanalyses arriving at mixed conclusions that, in aggregate, may suggest a modest weekend effect.…”
Section: Introductionmentioning
confidence: 87%
“…One study suggested factors related to service provision inside and outside the hospital and case-mix factors that may contribute to or modify the weekend effect [ 11 ]. In-hospital factors include lower staffing levels during weekends [ 2 ], delayed assessment and management, fewer ward rounds [ 12 ], and disparities in resources and expertise [ 3 ]. Pre-hospital factors include the timeliness of patient referral and the availability of ambulance service [ 11 ].…”
Section: Introductionmentioning
confidence: 99%